Protection of Rights and Freedoms of Minors in Employment: International Law and Experience of Ukraine - Pavlichenko, Olena; Ostapenko, Yuliya; Kryvenko, Dmytro; Fomina, Halyna; Lets, Olha (The Age of Human Rights Journal, 2023)
The issue of protecting the rights of minors is undoubtedly relevant. There is a tendency in society when the employment of minors in the labor market is growing. The purpose of the article is to analyze the theory and practice of legal regulation of labor of minors under Ukrainian and international law and to find the optimal solution to the problematic issues that exist in this area. The article deals with the legal features of the work of minors at the national and international levels. Universal international legal acts enshrine the fundamentals of protection of the rights of minors from forced labor and oblige states to set a minimum age for employment and prohibit minors from holding certain positions. National legislation extends the norms on the work of minors in accordance with their labor market, clarifies and expands the rights of minors and the employment procedure. Despite the fact that the rights of child workers are clearly regulated, the state should eliminate certain shortcomings to ensure the rights and freedoms of this group of workers. The authors conclude that the term "light work" needs to be clarified, and a detailed classification of child workers depending on their age and state benefits is necessary. It is necessary to take educational measures to inform minors about their rights in the field of employment, and to develop a simplified mechanism for the protection of their rights. Scientific work can contribute to consolidate Ukraine’s international relations with that of other countries in terms of developing bilateral relations to protect the rights of underage workers.